World Bank, Inter-American Development Bank, and subregional development banks in Latin America: Dynamics of a system of multilateral development banks - Fernando Prada (Asian Development Bank Institute (ADBI), 2012)
Multilateral development banks (MDBs) are an innovative institutional model to channel financing and knowledge to developing countries. In Latin America, the balance of forces between competition and collaboration among MDBs and other sources of development finance have formed a system that is decentralized and client-oriented. We analyze three types of relationships between MDBs to show areas of strength in their operations and future potential. For this, we use a great amount of quantitative data from the annual reports and financial databases of MDBs that the FORO Nacional Internacional research program has been tracking periodically. The three types of dynamics between these institutions are (i) division of labor between MDBs and comparative advantages; (ii) finding a balance between financial strength, internal costs, and development effectiveness; and (iii) deciding on the distribution of net income to create capacities to provide services to member countries.
Keywords: F34; O1; O19; 330; development finance; multilateral development banks; world bank; inter-american development bank; subregional development banks; latin america; Entwicklungsbank; Komparativer Vorteil; Entwicklungsfinanzierung; Internationale Bank; Lateinamerika